2021
DOI: 10.1108/ijshe-04-2021-0148
|View full text |Cite
|
Sign up to set email alerts
|

University students involved in a sustainable world: assessing sustainable consumption in Spain

Abstract: Purpose To achieve sustainable development to protect the environment and society, an increasing number of scholars have conducted in-depth research on sustainable and responsible consumption behaviors. The outputs demonstrate that consumers are increasingly concerned and aware of the issues associated with the excessive use of resources. The purpose of this paper is to analyze the validity and reliability of the Sustainable Consumption Scale (SC-S) in the Spanish context. Design/methodology/approach The ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 59 publications
(69 reference statements)
0
11
0
Order By: Relevance
“…Universities and other higher education institutions are currently more concerned with the environmental deterioration of the planet and, consequently, with the implementation of sustainable initiatives that feed the competence of action. Hence, in view of the context of the application of the scale for its validation, attention should be paid to the implementation of participatory methodologies for collective awareness of sustainability (Margaça, et al , 2022) and the environment in particular, providing people with civic awareness. Social responsibility, social and civic values not only guide the third mission of universities but also the institution’s activities, such as teaching and research (García-Gutierrez and Gaitero, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Universities and other higher education institutions are currently more concerned with the environmental deterioration of the planet and, consequently, with the implementation of sustainable initiatives that feed the competence of action. Hence, in view of the context of the application of the scale for its validation, attention should be paid to the implementation of participatory methodologies for collective awareness of sustainability (Margaça, et al , 2022) and the environment in particular, providing people with civic awareness. Social responsibility, social and civic values not only guide the third mission of universities but also the institution’s activities, such as teaching and research (García-Gutierrez and Gaitero, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…When evaluating pro-environmental personal values, this study contributes to the ongoing achievement of SDG 4 (Quality Education), SDG 12 (Responsible Consumption and Production) and SDG 13 (Climate Action) concretely. Being environmentally conscious and guided by values that preserve the sustainability of the planet is a challenge and, at the same time, crucial to establishing a commitment with global educational action-oriented and universally applicable SDG (Kautish et al , 2020; Margaça et al , 2022). For instance, studies point to the fact that values are influencing factors regarding consumption behaviors (Cho et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…By considering this theory, we can gain a comprehensive understanding of individuals' unobservable psychological states and thought processes, which allows us to predict their behavior [36,37]. Originally developed to explain preschoolers' understanding of beliefs and desires [38], the theory of mind has since been applied to sustainable consumption [2,[39][40][41]. Through the use of this theory, we can conceptualize sustainable consumption as a multidimensional construct shaped by cognitive, affective, and behavioral factors [2,42].…”
Section: Theoretical Approachmentioning
confidence: 99%
“…The model for HE enables to gain knowledge and insights of the community profiles to after conform with the terms of SDG 12: responsible production and consumption. Margaça et al [33] developed an assessment instrument, the SC scale which can promote the evaluation and prediction concerning a SC attitude.…”
Section: Identification Of the Main Topics To Teaching Andmentioning
confidence: 99%
“…Design for sustainability is a key part of SC and SP and HEIs have an intermediary position in spreading sustainability by design into industry and outreach activities along with educational actions and investigation, through which learning is used in solving difficult societal problems [56]. Margaça et al [33] refer that HEIs have shown a larger concern for expanding the range of sustainable policies and programs, both in curricula and in the development and conversion of infrastructures, to support SC and performed in-depth investigation on SC and responsible behaviours.…”
Section: Contribution Towards a Sustainable Consumption Behavioral Ch...mentioning
confidence: 99%